The effect of defects on strength of gold microparticles. (October 2019) - Flanagan, Tyler J.; Kovalenko, Oleg; Rabkin, Eugen; Lee, Seok-Woo
Abstract: Mechanical properties of solid-state-dewetted Au microparticles were characterized by microcompression tests. Our results revealed that large Au microparticles exhibit a strong size effect in yield strength, while the strength of their smaller counterparts reaches saturation and is size-independent. We discuss these two regimes in terms of source-controlled plasticity with a theoretical strength limit. Our calculations capture the particles behavior observed in the experiment, as well as predict the effects of sample geometry on the scaling law. This work shows that the microparticles produced by solid-state-dewetting method represent a convenient model system to study dislocation plasticity at small length scales. Graphical abstract: Unlabelled Image